Analysis of Determinants of Fashion Product Purchase Decisions on Aijostore.Id Denpasar - Ni Kadek Dwi Sri Nasih; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Consumers purchasing decisions emerge from evaluating alternatives and selecting the option that best satisfies needs and expected benefits. In marketing terms, these decisions are strategically important because they signal how effectively a firm captures attention, builds preference, and converts interest into transactions. This study examines whether viral marketing, affiliate marketing, and celebrity endorsements shape purchasing decisions among customers of Aijostore.id. Using a quantitative design, the population comprised consumers who had previously bought products through the Aijostore.id e-commerce platform. Data were collected from 96 respondents and analyzed through validity and reliability tests, classical assumption checks, multiple linear regression, multiple correlation analysis, the coefficient of determination, and hypothesis testing using F and t statistics. Results show that viral marketing, affiliate marketing, and celebrity endorsements each have a positive and significant effect on purchasing decisions, and their combined effect is also significant. Based on these findings, management is advised to strengthen celebrity endorsement strategies by ensuring a strong fit between the endorser’s image and the target market, and by maintaining consistency over time. Companies should also improve the credibility of viral content sources and apply tighter monitoring of affiliate programs to prevent misinformation, enhance accuracy of product claims, and sustain consumer trust overall.